ORIGIN OF LONG-CHAIN ALKANES AND ALKANOIC ACIDS IN ENDOLITHIC MICROBIAL COMMUNITY OF THE MCMURDO DRY VALLEYS, ANTARCTICA (ABSTRACT) (Twelfth Symposium on Polar Biology) - マツモト, ゲンキ; / ワタヌキ, クニヒコ; MATSUMOTO, Genki I.; FRIEDMANN, E. Imre; WATANUKI, Kunihiko (National Institute of Polar Research, 1991)
P(論文) departmental bulletin paper